LINGKAR KUASA KEHIDUPAN KOMUNITAS PEMULUNG PANDESARI KOTA MALANG - Amiruddin, Lutfi (Jurnal Kawistara, 2012)
Study of scavenger community of Pandesari, Malang becomes an importance research to describe deeply the social process the phenomena of scavenger is caused sometimes by local governmentâs policy neglects their condition. The urban people need residence and job, to avoid roverty many of than became scavenger. The scavengers are subordinated under the power of âbossâ. There are the sorter and the weigher who labored by the boss. There are four results of the paper. The ïrst result shows that the boss achieves power through the patron-client relationship. This relation places the scavengers as dependant to the boss. The second result shows that there has been exploitation occurred in scavenger community. The exploitation places the scavengers as the exploited faction, while the boss is the exploiting faction. The third result shows that the scavengers do resistance as the impact of the exploitation they suffer from. The fourth result is also criticism to Scottâs view in patron-client relationship that the sorter and the weigher are the members of community that are given a special authority from the elite power, with their role for strengthening the power of elite community. They are âthe right handâ of elite community who should strengthen and protect power.